2011
DOI: 10.5539/ass.v8n1p134
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Market Orientation and Learning Orientation in Improving Innovativeness and Performance of Small and Medium Enterprises

Abstract: The purpose of study is to describe contradiction relationship between market orientation toward organizational performance and to provide a quantitative analysis, in which learning orientation, market orientation, entrepreneurial orientation, and innovativeness function as the key success factors in technology-intensive firms. The authors formulate a structural equation model to examine the relationship among these constructs. A structural equation model was designed to examine the relationship. To test the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
110
1
20

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(141 citation statements)
references
References 46 publications
(71 reference statements)
10
110
1
20
Order By: Relevance
“…Most of these studies have found a strong positive correlation between market orientation and performance (Hooley et al, 2000;Shoman & Rose, 2001;Grainer & Padanyi, 2005;Olavarriete & Friedman, 2008;Li & Justin, 2008;Morgan et al, 2009;Dauda & Akingbade, 2010); though there are a small number of studies that found no positive linear relationship between market orientation and firm's performance (Au & Tse, 1995;Demirbag et al, 2006). Previous studies have suggested a direct relationship between market orientation and business performance, using the business environment as moderator (Suliyanto and Rahab, 2012). A review of the literature suggests that despite the many studies that have been undertaken to learn about market orientation, certain important variable such as the environment in which the business is conducted have not been given desired attention in the literature.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Most of these studies have found a strong positive correlation between market orientation and performance (Hooley et al, 2000;Shoman & Rose, 2001;Grainer & Padanyi, 2005;Olavarriete & Friedman, 2008;Li & Justin, 2008;Morgan et al, 2009;Dauda & Akingbade, 2010); though there are a small number of studies that found no positive linear relationship between market orientation and firm's performance (Au & Tse, 1995;Demirbag et al, 2006). Previous studies have suggested a direct relationship between market orientation and business performance, using the business environment as moderator (Suliyanto and Rahab, 2012). A review of the literature suggests that despite the many studies that have been undertaken to learn about market orientation, certain important variable such as the environment in which the business is conducted have not been given desired attention in the literature.…”
Section: Introductionmentioning
confidence: 97%
“…The measurement of firm performance and market orientations were adopted frm Suliyanto and Rahab (2012). A measure of business environment was adopted from the work of Abd Aziz (2011).…”
Section: Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, this study was driven as to further explore the importance of market orientation (MO) among service SMEs in Malaysia. Furthermore, the effects of MO on business performance generally need to be confi rmed (Cambra-Fierro et al 2012;Jain & Ali 2013;Mohammed Abdulai & Baba Yusif 2012;Suliyanto & Rahab 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Morgan et al (2009) also recommended for future researchers to assess the value of market orientation in organizations-especially on its measurement. Racela et al (2007: 146) ;Mokhtar et al (2009;Suliyanto and Rahab, 2012) all observed that, research on market orientation, as a concept, was still inadequate with limited studies in developing nations like Asia and Africa. Finally, there is a problem of limited studies on marketing managers, particularly on multinational business activities in developing African countries.…”
Section: Introductionmentioning
confidence: 99%